Women's attractiveness contingent self-esteem, romantic rejection, and body dissatisfaction. (December 2021) - Harrington, Auguste G.; Overall, Nickola C.
Highlights: Social standards of attractiveness put women at risk of body dissatisfaction'. Women high in Attractiveness Contingent Self-Esteem (ACSE) are particularly at risk. Romantic rejection provides negative feedback that also risks body dissatisfaction. High ACSE predicted more body dissatisfaction when women faced romantic rejection. Examining relevant contexts is important to understand risks of body dissatisfaction. Abstract: The centrality of attractiveness to social evaluations of women puts women at particular risk of body dissatisfaction. However, it is less clear who these social standards most affect and the situations in which they are most salient. Women whose self-esteem is more contingent on standards of attractiveness (ACSE) should be particularly vulnerable to body dissatisfaction, particularly in contexts that provide negative attractiveness-relevant feedback such as romantic rejection. The current research tested whether women higher in ACSE experienced greater body dissatisfaction in the context of naturally-occurring experiences of romantic rejection. In Study 1, women ( N = 168) identified and recalled a range of prior rejection experiences and reported their body dissatisfaction. Women higher in ACSE recalled greater body dissatisfaction in the context of romantic rejection. In Study 2, women ( N = 101) recorded daily experiences of romantic rejection and body dissatisfaction ( N = 885 daily records). Women higher in ACSE experienced greater within-person increases in body dissatisfaction on days they reported romantic rejection. The results emphasize the relevance of romantic rejection for understanding women's body dissatisfaction and help explain inconsistencies in the literature by illustrating that higher ACSE is associated with greater body dissatisfaction in contexts that provide negative attractiveness-related feedback.